Strengthening of the wooden structures - Ślósarz, Szymon (Budownictwo i Architektura / Civil and Architectural Engineering, 2020)
The paper is a review of the literature on the strengthening of wooden structures. The strengthening methods are classified according to their purpose and specifics. The article deals with both traditional methods commonly used and modern methods involving the use of composite materials. The paper also includes description of studies on various strengthening methods as well as the presentation of their results. The author also refers to the causes of the loss of load bearing capacity, causes of wood degradation and wooden structures durability in relation to operating conditions.